Climate-Driven Shifts in Wild Cherry (Prunus avium L.) Habitats in Türkiye: A Multi-Model Projection for Conservation Planning - Canturk, Ugur; Koç, İsmail; Erdem, Ramazan; Ozturk Pulatoglu, Ayse; Donmez, Sevgi; Ozkazanc, Nuri Kaan; Sevik, Hakan; Ozel, Halil Baris (MDPI AG, 2025)
Climate change poses a serious threat to biodiversity, particularly for woody species with limited dispersal capacity such as Prunus avium L. (wild cherry). In this study, we assessed potential shifts in its suitable distribution range (SDR) across Türkiye by applying an ensemble modeling framework that combined Generalized Additive Models (GAM), Maximum Entropy (MaxEnt), and Random Forest (RF). We used updated occurrence data (including GBIF and EUFORGEN records) and 11 ecologically relevant bioclimatic variables under SSP2-4.5 and SSP5-8.5 scenarios. Model performance was validated using AUC (Area Under the ROC Curve) and TSS (True Skill Statistic) metrics. Results suggest that while 60–70% of current SDRs remain stable by 2100, approximately 10% may be lost, with 20–23% new expansions. Temperature seasonality (Bio4) and seasonal precipitation (Bio15) were consistently identified as dominant predictors across models. Notably, newly suitable habitats are expected to be spatially isolated, limiting natural colonization. Our findings highlight the necessity of proactive conservation planning, including assisted migration and drought-resistant genotype selection, to ensure long-term persistence of wild cherry under changing climates. These results offer actionable insights for adaptive forest management and biodiversity conservation in Mediterranean-type ecosystems.
Keywords: Climate Change Adaptation; Random Forest; Generalized Additive Models; Maxent; Species Distribution Modeling